Comparative analysis of technical indicators for conventional and ecological agriculture - Alexandra Marina Brătulescu (Manolache); Alina Mărcuṭă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Conventional agriculture is characterized by intensive mechanization and chemization, making products competitive on the market of agricultural products, while organic farming is a "modern" process of growing plants, fattening animals and producing food, which stands out. fundamental of conventional agriculture. In this paper, the technical indicators for the two types of conventional and ecological agricultural systems will be analyzed. The analysis of the surfaces, the average productions as well as the total ones from the quantitative point of view will be carried out, with the help of the data provided by the National Institute of Statistics (INSSE) and the Institute of Research - Ecological Agriculture (FIBL). This analysis highlights the evolution or involution, retrospective and current situation for the two types of agricultural systems at national level, using the method of comparative analysis, in order to determine the direction of these agricultural systems.
Keywords: Q14; Q57; 330; evolution; conventional; ecological